Giant bilateral axillary artery aneurysms with left complete obstructive thrombus in intravenous immunoglobulin-sensitive Kawasaki disease: a case report - Chen Chu; Lan He; Yi-xiang Lin; Li-ping Xie; Fang Liu (BMC, 2021)
Abstract Background Kawasaki disease (KD) is a systemic vasculitis that predominantly affects medium-sized arteries. In addition to well-known coronary artery aneurysms (CAAs), peripheral systemic artery aneurysms (SAAs) have also been sporadically reported. In the literatures, SAAs occurred mainly in untreated, intravenous immunoglobin (IVIG)-resistant, or severe refractory KD, and thrombotic events in SAAs were rarely reported. Case presentation A 10-month-old boy with a history of KD was referred to our hospital for suspected pseudoaneurysm of the axillary arteries. Four months prior to presentation, he had persistent fever, conjunctival congestion, and rash. On the 10th day of fever echocardiogram showed biliteral CAAs. He was then diagnosed with KD and given IVIG 2 g/kg and aspirin at a local hospital. His fever and symptoms soon subsided and he was discharged with low dose aspirin and dipyridamole. One month prior to presentation, his parents incidentally palpated swellings in his bilateral axillae. On admission, physical examination revealed a pulsatile swelling in his right axilla and a non-pulsatile swelling in the left with impalpable left brachial and radial pulses, cooler and less active left upper limb than the right one. While the pulses of other three limbs were normal. Ultrasound examination revealed giant bilateral axillary artery aneurysms (AAAs) with massive thrombus in the left. Angiography confirmed giant bilateral AAAs with left AAAs completely occluded and fine collateral vessels connecting to the distal brachial artery, in addition to giant bilateral multiple CAAs without stenoses. The patient was given intravenous prostaglandin for 10 days to allow for formation of collateral circulation, as well as aspirin, low molecular weight heparin (which was switched to warfarin before discharge) and metoprolol. At discharge, the temperature and movement of his left upper limb improved significantly. On follow-up at 7 months, his left upper limb further improved and was similar to the right with no occurrence of cardiovascular events. The images of CAAs and AAAs on echocardiogram and computerized tomography remained the same. Conclusions This case highlights the importance of evaluating peripheral SAAs in KD patients with CAAs, even if their course of treatment appears smooth. For both large non-aortic SAAs and CAAs in KD patients, antithrombotic therapy is of utmost importance.